Meteorological data from Skogaryd Central, Mast-1 - Skogaryd Research Catchment (University of Gothenburg, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Skogaryd Research Catchment (2025). Meteorological data from Skogaryd Central, Mast-1, 2024-01-01–2024-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/yu3lfa2fhCtNTH3Wr6Cyj1lo
Keywords: Skogaryd Research Catchment; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Air pressure; Air pressure; Wind speed; Wind speed; Wind direction; Wind direction; Incoming shortwave radiation; Incoming shortwave radiation; Outgoing shortwave radiation; Outgoing shortwave radiation; Incoming longwave radiation; Incoming longwave radiation; Outgoing longwave radiation; Outgoing longwave radiation; Net radiation; Net radiation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap